2022
DOI: 10.1182/bloodadvances.2022007698
|View full text |Cite
|
Sign up to set email alerts
|

The Consortium on Newborn Screening in Africa for sickle cell disease: study rationale and methodology

Abstract: Sickle cell disease (SCD) is a common condition within sub-Saharan Africa and associated with high under-5 (U5) mortality. The American Society of Hematology instituted the Consortium on Newborn Screening in Africa (CONSA) for SCD, a seven-country network of sites to implement standardized newborn hemoglobinopathy screening and early intervention for children with SCD in sub-Saharan Africa. CONSA's overall hypothesis is that early infant SCD screening and entry into standardized, continuous care will reduce U5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…The network aims to show the benefits of NBS and early interventions for children with SCD in SSA countries. [73][74][75] Our study also showed the impact of nutritional supplementation on the clinical outcomes of children with SCD. Malnutrition and SCD are the prevalent non-communicable diseases in SSA, and the effect of poor nutrition is worse among children living with SCD.…”
Section: Discussionmentioning
confidence: 74%
“…The network aims to show the benefits of NBS and early interventions for children with SCD in SSA countries. [73][74][75] Our study also showed the impact of nutritional supplementation on the clinical outcomes of children with SCD. Malnutrition and SCD are the prevalent non-communicable diseases in SSA, and the effect of poor nutrition is worse among children living with SCD.…”
Section: Discussionmentioning
confidence: 74%
“…Unfortunately, many testing facilities in Africa lack quality assurance programmes or have inadequate ones, which can lead to errors in testing and misdiagnosis. 56 Quality assurance programmes not only need specimens with known values to measure along with patient specimens but also involve regular checks of equipment, reagents, and personnel performance, as well as ongoing training and education of staff on quality assurance practices. Quality assurance includes standardisation and harmonisation in testing protocols between laboratories and between countries.…”
Section: Discussionmentioning
confidence: 99%
“…These measures may encompass the establishment of localized or nationwide public health outreach initiatives, the cultivation of collaborative efforts among consortiums, the provision of directives for standardized data collection and analysis, and the promotion of shared methodologies for dissemination and training. Every country is urged to formulate a tailored strategy that aligns with its specific national conditions [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%